Dispersive liquid–liquid microextraction versus single-drop microextraction for the determination of several endocrine-disrupting phenols from seawaters - López-Darias, Jessica; Germán-Hernández, Mónica; Pino, Verónica; Afonso, Ana M. (Talanta (Oxford), 2010)
Two liquid-phase microextraction procedures: single-drop microextraction (SDME) and dispersive liquid–liquid microextraction (DLLME), have been developed for the determination of several endocrine-disrupting phenols (EDPs) in seawaters, in combination with high-performance liquid chromatography (HPLC) with UV detection. The EDPs studied were bisphenol-A, 4-cumylphenol, 4-tertbutylphenol, 4-octylphenol and 4- n-nonylphenol. The optimized SDME method used 2.5 μL of decanol suspended at the tip of a micro-syringe immersed in 5 mL of seawater sample, and 60 min for the extraction time. The performance of the SDME is characterized for average relative recoveries of 102 ± 11%, precision values (RSD) < 9.4% (spiked level of 50 ng mL −1), and detection limits between 4 and 9 ng mL −1. The optimized DLLME method used 150 μL of a mixture acetonitrile:decanol (ratio 15.7, v/v), which is quickly added to 5 mL of seawater sample, then subjected to vortex during 4 min and centrifuged at 2000 rpm for another 5 min. The performance of the DLLME is characterized for average relative recoveries of 98.7 ± 3.7%, precision values (RSD) < 7.2% (spiked level of 20 ng mL −1), and detection limits between 0.2 and 1.6 ng mL −1. The efficiencies of both methods have also been compared with spiked real seawater samples. The DLLME method has shown to be a more efficient approach for the determination of EDPs in seawater matrices, presenting enrichment factors ranging from 123 to 275, average relative recoveries of 110 ± 11%, and precision values (RSD) < 14%, when using a real seawaters (spiked level of 3.5 ng mL −1).